ROOCK (CORVUS FRUGILEGUS L.) IN THE CITY OF ODESA: PATHS OF SYNANTHROPISATION AND ECOLOGICAL FEATURES OF EXISTENCE - Ківганов, Дмитро; Стойловський, Володимир; Чобану, Михайло (SWorldJournal, 2025)
The article examines the process of synanthropization of the Rook (Corvus frugilegus L.) within the urban landscape of Odesa, Ukraine. This phenomenon is part of a broader, well-documented trend of corvid urbanization across Europe, which intensified duri